Assessment of Physical Fitness after Bariatric Surgery and Its Association with Protein Intake and Type of Cholecalciferol Supplementation - Hendrika J. M. Smelt (Medicina, 2019)
Background and objectives: Several studies showed that there is a relationship between vitamin and mineral status and muscle strength. In particular this is the case for handgrip strength (HS) and vitamin D deficiency. In bariatric surgery there is a risk of decrease in muscle strength after surgery and also vitamin and mineral deficiencies are not uncommon. The aim of this study is to assess the effect of low vitamin 25 (OH) cholecalciferol levels, high dose cholecalciferol supplementation regime and protein intake on physical fitness, measured using handgrip strength (HS) and the shuttle walk run test (SWRT). Materials and Methods: For this retrospective study, 100 patients who have had bariatric surgery were included. Group A (n = 50) used 800 IU oral cholecalciferol per day. Group B (n = 50) used 800 IU oral cholecalciferol daily and 50,000 IU liquid cholecalciferol monthly lifelong. Both groups were matched on common variables. To measure physical fitness, we used the HS manometer of Jamar and the Shuttle Walk Run Test (SWRT) to assess physical capacity. Results: No significant differences in HS and SWRT outcomes were found between patients with serum 25 (OH) cholecalciferol < 75 nmol/L or >75 nmol/L. The postoperative HS is significantly influenced by protein intake (p = 0.017) and no significant influence was seen in outcomes of the SWRT (p = 0.447). Conclusion: We have found that serum 25 (OH) cholecalciferol and different cholecalciferol supplementation regimes do not have a significant effect on HS and SWRT before, three and 6 months after surgery. It seems that protein intake plays a more important role in maintaining adequate muscle strength.